ANALISIS KUALITAS PELAYANAN HAJI DAN UMROH PADA KANTOR KEMENTERIAN AGAMA KABUPATEN SITUBONDO TAHUN 2019 - Ratna Koba Susanti; Eki Oktaviani Zaini (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Abdurachman Saleh Situbondo, 2019)
In yuhlic .service.s, citizen.s had the same righi to ohtain qualiry services. Thi.s stud y aimed to determine the qualiry of Hajj and tlmrah services ar the Ministry n/fiefiginu.s Affairs Situhondo R• R• ncy. Tim.s research was quantitative stud y with curve y research u.sink Nirpsimrnnn.s .service qualiry dimension.s. The re.search location was Ministry n/ be/idiom.s Affairs Situhondo Regenc y on PB Sudirman Street No. 4 Situhondo. The yoyulation in ihi.s .srudJ we.s the rem.srrnnr.s of hajj‘ or the haJj and umroh .service department of the Ministry nf Religion.s Affair.s Situhondo Regency in the data of January -March 2019 which were 314 yeoyle. The .sampling of the re.search using Slovin formula, with the total of 76 re.spondenr.s. Retrieval of data used que.stionnaire. Data analy.si.s in clii.s .study used .servqual with measurement /rvef.s using 5-level Likert .scale. Thi.f .srody used five dinten.sion.s of .service qualiry, name1y rmipiñ Ice, reliahiliry, re.sion.sivenr.s.s, a.s.surance, and empathy. The value of .srrvicr qualiry was obtained from the yerceyiion value of the rem.srrnnr minus rd value n/ eryrcrnrinn.s. The re.sufr.s showed thai the qualiry of .sorrier.s provided hy the hajj’ and umroh service department of the Ministry of Religious Amir.s Situhondo Regenc y .showed servqual value of -20.54, which could he categorized as yoor servicequalit y.